Decision taking as an essential professional ability in the Medical career - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
Taking as a starting point the logic of the professional’s performance of the comprehensive general doctor and the relationship between medical decision taking and the abilities in the curricular design of the Medical Career it is possible to identify the essence of the main professional abilities in medical decision taking. The considerations that medical decision taking first deal with diagnostic actions related to the patient’s health problem and a later with actions to restore the patient’s health by solving their medical problem, make medical decision taking abilities as the core of the professional logic abilities that allows doctors to fulfill with their function of giving comprehensive medical assistance to their patients. References about medical decision taking as a professional ability and its main essence has not been found in the medical literature up to the present.